2021
DOI: 10.1080/02699052.2021.1953593
|View full text |Cite
|
Sign up to set email alerts
|

Post-concussion symptoms three months after mild-to-moderate TBI: characteristics of sick-listed patients referred to specialized treatment and consequences of intracranial injury

Abstract: Post-concussion symptoms three months after mild-to-moderate TBI: characteristics of sick-listed patients referred to specialized treatment and consequences of intracranial injury, Brain Injury,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…There were few missing items, with no variable missing more than 3%. The baseline characteristics of the sample are presented in Table 1 and thoroughly described elsewhere 35. Of the 113 patients, 11 were still on 100% sick leave at 1 year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were few missing items, with no variable missing more than 3%. The baseline characteristics of the sample are presented in Table 1 and thoroughly described elsewhere 35. Of the 113 patients, 11 were still on 100% sick leave at 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline E4 Journal of Head Trauma Rehabilitation/January-February 2023 characteristics of the sample are presented in Table 1 and thoroughly described elsewhere. 35 Of the 113 patients, 11 were still on 100% sick leave at 1 year. Additional work-related data on 95 patients at 1 year are provided in Appendix 2 (Supplemental Digital Content, available at: http://links.lww.com/JHTR/A530).…”
Section: Resultsmentioning
confidence: 99%
“…However, the study participants had sustained mild-to-moderate TBIs, and their knowledge of personal work-related data was not suspected to be notably affected. In addition, neuropsychological assessment at baseline showed that severe memory or attention problems were not present to such a degree that one would expect invalid reports [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Structured Diagnostic Interview, included in the SACA, will be used to establish the mTBI history, including duration of loss of consciousness, alteration of consciousness, and posttraumatic amnesia [ 47 ]. The interview ends with the Neurobehavioral Symptom Inventory [ 56 ]. The California Verbal Learning Test-II (CVLT-II) [ 57 ] will be used to assess verbal memory, a cognitive domain affected by mTBI.…”
Section: Methodsmentioning
confidence: 99%